Life Stories of Mathematics Teacher Histórias de Vida de Professores de Matemática - Emerson Rolkouski (Universidade Estadual Paulista, 2008)
The objective of this work is to understand how a Mathematics teacher becomes the teacher of Mathematics that he is. In other words, to understand how the individual becomes, through his life, his relationship with other individuals, this teacher of Mathematics, with these ideas, practices, and resistances. Four Mathematics teachers, with different degree levels, were interviewed according to the methodological parameters of the Oral History. Their testimonies allowed the composition of a scenary wich made it possible to extend the comprehension concerning becoming "the" Mathematics teacher. Their life stories were read with differentiated lenses. Under a sociological focus, based on Norbert Elias and Pierre Bourdieu's works, under the perspective of psychology, based on Jerome Bruner's works and finally a last reading denominated scientific-literary, in which the testimony is read through the analogy of literary texts. These readings presented, considerations were made on their possibilities and impossibilities facing the understanding of "how a teacher of Mathematics becomes 'the' teacher of Mathematics that he is". Key Words: Mathematic Education. Oral History. Teachers Formation. O objetivo deste trabalho é compreender como um professor de Matemática torna-se o professor de Matemática que é. Ou seja, compreender como o indivíduo vai se tornando, ao longo de sua vida, de sua relação com outros indivíduos, este professor de Matemática: com estas idéias, práticas, resistências. Quatro professores de Matemática, com diferentes níveis de titulação, foram entrevistados segundo os parâmetros metodológicos da História Oral. Seus depoimentos permitiram a composição de um cenário que possibilitou ampliar as compreensões acerca do tornar-se "o" professor de Matemática. As histórias de vida dos depoentes foram lidas com lentes diferenciadas: sob um enfoque sociológico, fundamentado nos trabalhos de Norbert Elias e Pierre Bourdieu, sob a perspectiva da psicologia, fundamentado nos trabalhos de Jerome Bruner e, finalmente, uma última leitura denominada de científico-literária, em que se lê o depoimento em analogia com textos literários. Apresentadas essas leituras, foram feitas considerações sobre suas possibilidades e impossibilidades frente à compreensão do "como um professor de Matemática torna-se 'o' professor de Matemática que é". Palavras-chave: Educação Matemática. História Oral. Formação de Professores.